A simulation program for Mobile Robot in open GL - Teuku Firsa; Zahari Taha; Raja Ariffin; Yap, Hwa Jen (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 14th - 15th May 2005 at Putra Palace Hotel, Kangar, Perlis.